Clinical aspects of urogenital atrophy in women - Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Female urogenital atrophy increases with the menopausal age. It is also susceptible to various types of hormonal therapy, e.g. systemic menopausal hormonal therapy and vaginal hormone therapy. Tibolone, a synthetic steroid with the affinity to all the basic types of steroid receptors – oestrogen, progesterone and androgen, is a good (i.e. effective and safe) alternative option to other therapies of atrophic lesions of the lower urogenital tract in women.